Mayday! Mayday! What critical communication skills are needed for young aviators? - Aina Suriani Mahmood; Noor Saazai Mat Saad; Nurhayati Mohd Nur (Education Policy and Development, 2023)
Communication is one of the fundamental factors in operating complex and highly regulated industries such as aviation maintenance. Aviation graduates' job performance and career development are highly dependent on their communication skills. However, the transition from student to aviation worker requires individuals to adapt to new communication practices in the workplace. Therefore, this study was conducted to identify the oral and written communication activities that the young aviation personnel in the aviation industry frequently encounters. In addition, this study was also conducted to find out what challenges they face in terms of communication. Nine participants, young aircraft maintenance technicians and License Aircraft Engineers (LAE), were involved in semi-structured interviews. Data were analyzed thematically and managed using ATLAS.ti software. The results show that the English language is critical for the development of professional communication skills among young aircraft maintenance technicians, as they need English language skills for oral and written activities. The identified needs and challenges in communication skills would help aviation institutions develop solutions to meet the aviation industry's needs.